Hey there!!!
Given equation - 3x+6y
x is given as -3
y is given as 6
Plugin these values to get the final answer
3 ( -3 ) + 6 ( 6 )
-9 + 36
= 27
27 is the final and the required answer
Hope my answer helps!
Answer:
n=0
Step-by-step explanation:
Rearrange
10+2=8−2+10
2+10=8−2+10
Combine like terms
2n+10=<u>8n−2n</u>+10
2+10=<u>6</u>+10
Subtract from both sides
2+10=6+10
2+10<u>−10=</u>6+10<u>−10</u>
Simplify
2n=6n
Subtract both sides from 6n of the equation
2=6
2<u>−6</u>=6<u>−6</u>
Solution
n=0
The given trinomial can be factored using the factorization method.
x² + 15x + 56
= x² +8x +7x + 56
= x(x+8) + 7(x+8)
= (x+8)(x+7)
Thus, (x+8)(x+7) is the factored form of the polynomial.
So the correct answer is option B
Answer:
C and F
Step-by-step explanation:
Those two just work, that simple
The minimum function determines the lowest number in a range!